Perlindungan Hukum Terhadap Merek Terkenal Dari Tindakan Pelanggaran Merek/Merek Tiruan Di Medan (Studi Undang-Undang No. 20 Tahun 2016 Tentang Merek Dan Indikasi Geografis) - Siti Nur Suflah (Iuris Studia: Jurnal Kajian Hukum, 2021)
Legal protection is a protection given to the subject law in the form of legal instruments, both preventive and repressive nature, both written and unwritten. Many trademarks circulating in the national market have similarities between one brand and another, both in general and in general, and this is an act that is clearly detrimental to the State and the entrepreneur who holds the rights. the brand. The type of research method used in this research is normative juridical research, namely research on the applicable laws and regulations in this case is Law no. 20 of 2016 concerning Brands and Geographical Indications. . The nature of this research is descriptive analytical where this research seeks to describe, describe and analyze the problems that arise, then look for the correct answer as a solution to the problem. The results of the discussion of the issue of the presence of the 2016 trademark law are useful for improving protection for brand owners and also providing adjustments to the development of intellectual property in Indonesia. The application of legal protection for well-known marks in Indonesia is important to ensure legal certainty from well-known brand rights holders that have been recognized by the state, a little guarantee of legal protection for well-known marks is currently contained in Article 21 of Law number 20 of 2016 concerning Marks and Indications. Geographically along with the explanation, then in Article 84 of the Minister of Law and Human Rights number 67 of 2016 concerning Trademark Registration and finally in the Statute of the Supreme Court number 022/HKI/2012, legal protection can be implemented if there is awareness from the public regarding well-known marks and the creation of a legal culture of obedient Indonesian society ( obey the law)